Lições de arquitetura através da transformação do espaço residencial: flexibilidade, adaptabilidade e tecnologia no desenho da habitação - Sabine Ritter De Paris (2022)
Living space involves as cultural and social space the different activities of daily life. Besides meeting basic needs as shelter, housing is also a place of work and leisure. The family group and the cultural aspects of society have undergone constant and rapid transformation, while the occupation of cities is increasingly dense and urban centers suffer scarcity of land. Ensuring the adaptability and flexibility of housing is essential to keep pace with users' changes. The contact with digital media and the recent technological innovations provide the capacity for interpretation and adaptation of society and the architect in the creation of contemporary adaptable architecture. This research seeks to understand how the strategies used in the flexibilization and the conditioning factors for the adaptation of the residential space affect in different ways the housing design. The objective is to assess the adaptability and flexibility of residential space and the effects of technologies on the transformation of ways of living. Likewise, to understand how technological innovations modify and contribute to improve flexibility and adaptability in housing. By means of Evaluation Rates calculated by the Analytic Hierarchy Process (AHP) multi-criteria method and with the data collected by means of the Revit software and developed algorithm on Dynamo plugin, the criteria of residential projects are analyzed. The algorithm as an innovative and complementary tool to the creative process and graphic methods present in the architect's profession, seeks quantitative data beyond the geometric universe. The application of the evaluation in case studies allowed to identify the deficiencies of the projects to be sought within the current technologies, solutions that would allow flexibility and adaptation within existing constructions. The relevance of a previous planning about the composition, choice of materials and industrial processes is primordial for the housing design. The digital trend appears as a tool that temporarily creates new spaces and brings new sensations. In the physical aspect, the technologies focus on lighter materials and easy assembly, which depend on adequate dimensions of housing spaces, as well as their distribution in the design process. The theoretical foundations on designing the residential space are the same, but the way they are applied is distinguished by the current interpretation of social, economic and technological scenarios.